Legal Protection for Doctors Performing Pregnancy Termination for Anencephalic Fetuses as Viewed from Undang-Undang Number 17 of 2023 on Health - Yusrawati Yusrawati; Chepi Ali Firman Zakaria; Hadi Susiarno (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Legal protection for healthcare professionals is a critical issue, particularly concerning pregnancy termination procedures involving medical emergencies. This study focuses on how Indonesian law regulates pregnancy termination in cases involving anencephalic fetuses, especially when the gestational age exceeds 14 weeks, and examines the protection afforded to doctors and the practical challenges they face. The research aims to analyze the legal framework provided under Law Number 17 of 2023 on Health and assess its implementation in the field. Method: Using a juridical-normative and empirical-juridical approach with a descriptive-analytical method, this study utilizes primary data from interviews with doctors, legal scholars, and religious figures, and secondary data from relevant laws and academic literature. Result: The findings reveal that while the law allows pregnancy termination under 14 weeks for medical emergencies or pregnancies from sexual violence, it lacks clear provisions for cases exceeding 14 weeks, such as anencephaly. Although anencephaly poses a serious medical risk, legal uncertainty persists for healthcare workers who perform terminations after this threshold. Conclussion: Terminations conducted following medical standards and with consent should not be criminalized. Therefore, legal reforms and clearer regulatory guidelines are essential to ensure adequate protection for medical personnel handling such exceptional cases.